Assessing Organization Agility Creating Diagnostic Profiles to Guide Transformation - Worley, Christopher G. (Wiley, 2014)
implementation The current pace of technical, competitive, and environmental change is faster than ever before, and response requirements are far more complex and sophisticated. In this turbulent environment, agility can mean the difference between success and stagnation. Assessing Organization Agility asks the questions and provides the answers that lead to better organizational reflex and more effective response
Description based on publisher supplied metadata and other sources
Keywords: Wirtschaft; Ability -- Testing; Business; Management